Think Talk Write Method Implementation to Improve Reasoning Skill (Universitas Negeri Semarang, 2018)
This research aim is to improve fourth-grade students' reasoning skill by using Think Talk Write method implementation. This research type was using Classroom Action Research (CAR). The research subject is the fourth-grade students at SD Negeri Jetak 01 in 2017/2016 academic year. Data collection technics are used observation, reasoning skill rubric assessment, and reasoning skill test. The research result is, Think Talk Write method is able to improve students' reasoning skill in thematic learning about 18.7 % from Pre Cycle to Cycle I. The reasoning skill test mean at Pre Cycle is 67.4 (in Fair category) and increased to 76.7 at Cycle I (in Average category), then it more increased to 86.1 (Good category) at Cycle II.Keywords: Think Talk Write method, reasoning skill, thematic learning.